Provision and Accessibility of Services of General Interest in Functional Urban Regions: The Case of Zagreb, Croatia - Ivan Šišak; Aleksandar Lukić (Land)
The quality of life in both urban and rural areas is highly dependent on the availability of services of general interest. This study examines the provision and accessibility of 41 types of point-specific services, divided into 10 categories, within the functional urban region of Zagreb, Croatia, characterized by a declining population, despite being the most populous area in Croatia. This study adopts a multi-service rather than a single-service research approach, providing a more comprehensive understanding of the phenomenon. Using GIS composite indices for service provision and accessibility by car (cumulative opportunities) were calculated. Cluster analysis (Ward method, quadratic Euclidean distance) revealed seven different geographical patterns. The results show different patterns of service provision and accessibility throughout the urban region. Two specific areas were highlighted: traditional and inner peripheral areas with low levels of both service provision and accessibility, and suburban areas with very good accessibility but very poor service provision. The results of this study are particularly valuable as they relate to a single functional urban area that includes both urban, suburban and rural settlements of different types, a spatial framework that has not been sufficiently analysed in the literature.